2012
DOI: 10.1063/1.3685448
|View full text |Cite
|
Sign up to set email alerts
|

Formation of carriers in Ti-oxide thin films by substitution reactions

Abstract: Conductive Ti-oxide thin films are produced using a reactive sputtering and post-annealing process. The lowest resistivity of Ti-oxide thin films (2.30 × 10–2 Ω-cm) can be achieved after annealing for 1 h at 400 °C in ambient O2. Additionally, the Hall measurement results indicate that the carrier concentration increases during the initial 1-h annealing process before decreasing during subsequent annealing. By curve fitting the Ols core-level peaks in the x ray photoelectron spectroscopy (XPS) spectrum of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The Ti 2p profiles exhibit the two characteristic peaks at 458.24 and 464.1 eV attributed to Ti 2p 3/2 and Ti 2p 1/2 binding energies, respectively. This reveals that Ti is in the Ti 4+ state (Figure c) Figure d shows the O 1s core spectrum and it consists of two peaks at 529.3 and 531.5 eV due to the presence of lattice oxygen species and surface-adsorbed oxygen species, respectively.…”
Section: Resultsmentioning
confidence: 95%
“…The Ti 2p profiles exhibit the two characteristic peaks at 458.24 and 464.1 eV attributed to Ti 2p 3/2 and Ti 2p 1/2 binding energies, respectively. This reveals that Ti is in the Ti 4+ state (Figure c) Figure d shows the O 1s core spectrum and it consists of two peaks at 529.3 and 531.5 eV due to the presence of lattice oxygen species and surface-adsorbed oxygen species, respectively.…”
Section: Resultsmentioning
confidence: 95%
“…2, which was prepared using data from a previous paper by Cha et al [11] In the XPS Ce 3d spectra, we re-determined that V 2 O 5 -CeO 2 /CVC-TiO 2 has a larger intensity area of Ce 3+ ions than V 2 O 5 -CeO 2 /P25-TiO 2 . Liu et al [14] reported that Ti 3+ creates a free carrier (%electron) when oxidized to Ti 4+ . In addition, according to previous studies by Cha et al [13,16], the TiO 2 synthesized via CVC had a higher ratio of Ti 3+ ions and contained more free carriers, and had a clear effect on the oxide ion state of the loading material.…”
Section: Resultsmentioning
confidence: 98%
“…The core level binding energy of 74.2 eV of Al 2p suggested the occurrence of Al 3+ in oxidation state. It is to be noted that the core levels binding energies Ti 2p 3/2 and Ti 2p 1/2 were 458.2 eV and 464.0 eV respectively in DC magnetron sputtered TiO 2 films [15,16], while in DC magnetron sputtered (Ta 2 O 5 ) 0.85 (TiO 2 ) 0.15 films the binding energies were 458.7 eV and 464.3 eV [17]. The chemical composition of the asdeposited films was determined from the core level binding energy peak area and the sensitivity factors of the constituent elements of aluminum, titanium and oxygen [18].…”
Section: Resultsmentioning
confidence: 99%